Development of Pico-Hydro Electric Power Plant on Irrigation Canal - Case Study: Menaming Village, Indonesia - Yuli Handika Hasyim; Asral Asral; Fri Murdiya (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
One potential that can be utilized as a source of small-scale electrical energy is irrigation canals. The obstacle experienced to utilize irrigation canals is because irrigation canals have low flow speeds and height differences in irrigation canals. In this study, a power plant was made in an irrigation stream with a flow speed of 0.3 m/s and a height difference of only 0.3 meters. This research began with a survey of the design and manufacture of waterwheels, transmission systems, and generators. After all components are installed, the generator output voltage measurement is carried out using lamp loads of 3,6,9,12,25 and 49 Watts. From the measurements, it can be seen that as the load increases, the rotation of the wheel, voltage, and frequency will also decrease. This is due to the lack of water power so that the water is no longer able to turn the waterwheel.